A 5.9-mJ 500-Hz Electro-Optic Q-Switched 1053 nm Nd：LiLuF4 Laser - 杨琦 朱小磊 陆婷婷 马剑 杭寅 陈卫标 (中国物理快报：英文版, 2014)
An efficient and high power 1053 nm electro-optic Q-switched Nd：LiLuF4 laser, end-pumped by two fiber coupled laser diodes at wavelength 806 nm, is reported for the first time. With an incident pump power of 24.4 W, the maximum laser output power of 7.3 W is achieved in free-running mode, and the optical conversion efficiency is 29.8%. For the Q-switched operation, the shortest pulse width of 17ns is obtained at the pulse repetition rate of 500 Hz, corresponding to the pulse energy of 5.9mJ with the peak power of 0.35 MW.